Elevation of serum KL‐6 in patients with psoriasis treated with anti‐tumour necrosis factor‐α therapy. (1st January 2016) - Higashi, Y.; Tada, K.; Shimokawa, M.; Kawai, K.; Kanekura, T.
Summary: We report three patients with psoriasis whose serum level of Krebs Von Den Lungen (KL)‐6 increased during therapy with anti‐tumour necrosis factor (TNF)‐α. A diagnosis of early‐phase or subclinical interstitial pneumonia was made in two patients, and their KL‐6 level decreased after anti‐TNF‐α discontinuation. The rise in KL‐6 in the other patient was attributed to methotrexate. We propose that serum KL‐6 should be monitored routinely in patients treated with anti‐TNF agents.